European Digital Mathematics Library - Rákosník, Jiří; Pavlov, Radoslav (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2013)
The aim of this paper is to survey the European Digital MathematicsLibrary project goals and achievements as well as an outlook for sustainable development.
Keywords: Digital Mathematical Library; Open Access; Institutional Repositories; DSpace; Publishing